EPIDEMIOLOGICAL STUDY OF TYPHOID FEVER PREVALENCE AMONG SUSPECTED CASES IN RAWALPINDI AND ISLAMABAD: IMPLICATIONS FOR PUBLIC HEALTH INTERVENTION - YASMEEN , S; PARVEEN , T; NAZAR , K (Biological and Clinical Sciences Research Journal, 2024)
Typhoid fever remains a significant public health concern in Pakistan, particularly in urban areas such as Rawalpindi and Islamabad. Understanding the prevalence of this disease is crucial for informing public health interventions and resource allocation. This study aims to determine the prevalence of typhoid fever among patients suspected of the disease in District Rawalpindi and Islamabad. A cross-sectional study was conducted over three months, from November 2011 to January 2012. A random sample of 500 patients suspected of typhoid fever was collected from various regional hospitals and clinical laboratories. Samples were tested using the Widal test or Typhi dot, and data on patient demographics and test results were recorded. Descriptive statistics, including frequencies and percentages, were used to summarize the data. Prevalence rates were calculated, and subgroup analyses were conducted to explore variations in prevalence among different age groups. Of the 500 samples collected, 95 tested positive for typhoid fever, yielding an overall prevalence rate of 19%. Subgroup analysis revealed that 31.5% of positive cases were in adults, while 68.5% were in children under the age of 15 years. Among children, the prevalence rates varied across different age groups, with 13.8%, 55.3%, and 30.7% of positive cases reported in 1-4 years, 5-12 years, and 12-15 years, respectively. Further analysis estimated the total prevalence of typhoid fever in Rawalpindi and Islamabad, revealing a prevalence rate of 685 per 10,000 individuals among children. This study highlights the significant burden of typhoid fever in Rawalpindi and Islamabad, particularly among children. The findings underscore the importance of targeted interventions to control the spread of the disease, including vaccination campaigns and improved sanitation measures. Continued surveillance and monitoring are essential for tracking trends in typhoid prevalence and guiding regional public health strategies.